BrazIliaN Type 1 & 2 DiabetEs Disease Registry (BINDER): longitudinal, real-world study of diabetes mellitus control in Brazil - de Almeida-Pititto, Bianca; Eliaschewitz, Freddy G.; de Paula, Mauricio A.; Ferreira, Graziela C. (Frontiers in Clinical Diabetes and Healthcare, 2022)
Introduction: This study aimed at assessing patterns of care and glycemic control of patients with DM in real life during a follow-up of 2 years in the public and private health sectors in Brazil. Methods: BINDER was an observational study of patients >18 years old, with type-1 (T1DM) and type-2 DM (T2DM), followed at 250 sites from 40 cities across the five regions of Brazil. The results for the 1,266 participants who were followed for 2 years are presented. Main results: Most patients were Caucasians (75%) and male (56.7%). 52% T1DM and 26.8% T2DM patients were from public hospitals. Treatment for T2DM consisted of biguanide (77%), sulfonylureas (33%), DPP4 inhibitors (24%), SGLT2-I (13%), GLP-1Ra (2.5%), and insulin (27%), with percentages not changing during follow-up. In addition to insulins (NPH in 24%, regular in 11%, long-acting analogues in 58%, fast-acting analogues in 53%, and others in 12%), T1DM received biguanide (20%), SGLT2-I (4%), and GLP-1Ra (<1%). After 2 years, 13% of T1DM patients were using biguanide, 9% SGLT2-I, 1% GLP-1Ra, and 1% pioglitazone. The use of NPH and regular insulins decreased to 13% and 8%, respectively, while 72% were receiving long-acting insulin analogues, and 78% fast-acting insulin analogues. HbA1c at baseline and after 2 years of follow-up was 8.2 (1.6)% and 7.5 (1.6)% for T1DM, and 8.4 (1.9)% and 7.2 (1.3)% for T2DM, respectively. After 2 years, HbA1c <7% was reached in 25% of T1DM and 55% of T2DM patients from private institutions and in 20.5% of T1DM and 47% of T2DM from public institutions. Conclusion: Most patients did not reach the HbA1c target in private or public health systems. In 2-year follow-up, there were no significant improvements in HbA1c in either T1DM or T2DM, which might indicate an important clinical inertia.